Recommendation of Information Architecture Design on Higher Education Institution Website Using Card Sorting Approach on Goal-Directed Design Method - Mira Kania Sabariah (School of Computing, Telkom University, 2016)
From the beginning of its discovery, website has been improving its function, one of which is as publication media. Also in the world of education, most of higher education institution employ the website to publish their school and to offer related information to their user. However, many disputes come to the user when using the website due to lack of both usability standard and information architecture design. Thus, this research focuses on a standard of information architecture design which is user-oriented to improve 5 aspects of website usability of the institution. Card sorting is used to arrange the information architecture in line with user expectation while goal-directed design functions to design user interface based on user’s goal. The conducted test is Usability Test which has formerly been undertaken on the research. The usability value of students and their parents who use higher education institution website designed by Card Sorting Method can be improved to 71.2% which is higher than the average standard. That is means, user involvement in defining the information architecture is very important for website usability can be achieved.